PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA MARTABAK BANGKA PINANG SEBATANG - Siti Nur Haliza Oktavia; Dadan Abdul Aziz Mubarok; Rama Chandra Jaya (Universitas Persada Indonesia YAI, 2025)
This study aims to investigate the extent to which product quality and service quality influence customer satisfaction at Martabak Bangka Pinang Sebatang. The research employed a quantitative approach, utilizing a survey technique as the main instrument for data collection. Primary data were gathered from 100 respondents who had previously made purchases, selected using a reasoned sampling method. The dataset was subsequently examined through multiple linear regression analysis, assisted by SPSSversion 27. The empirical results indicate that product quality emerges as a dominant determinant of customer satisfaction, supported by a significance level below 0.001 and a t-statistic of 8.472, reflecting a robust statistical relationship. In parallel, service quality was also found to have a statistically significant and positive effect on customer satisfaction, as demonstrated by a significance value of 0.004 and a t-value of 2.964. Moreover, when both independent variables were analyzed concurrently, product quality and service quality collectively exhibited a significant impact on customer satisfaction, as evidenced by an F-value of 39.711 and an R² value of 0.461. These findings underscore that systematic enhancement of both product quality and service quality constitutes a crucial strategic foundation for improving customer satisfaction and reinforcing competitive positioning within the culinary business sector